2011
DOI: 10.1159/000325505
|View full text |Cite
|
Sign up to set email alerts
|

<i>KLOTHO</i> Gene Polymorphism of G395A Is Associated with Kidney Stones

Abstract: Background/Aims: KLOTHO, a type-1 transmembrane protein with glucurodinase activity, is expressed in tissues responsible for calcium homeostasis such as the kidney, parathyroid gland and the epithelium of the choroid plexus in the brain. Given the emerging evidence indicating a novel regulatory function for KLOTHO protein in renal calcium and phosphate homeostasis, the present study aims to investigate the association between KLOTHO genetic polymorphisms and kidney stone (KS). Methods:KLOTHO gene polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 47 publications
0
22
1
Order By: Relevance
“…In previous studies, the frequencies of the A allele in the G-395A SNP varied from 0.155 (Kim et al, 2008) to 0.171 (Rhee et al, 2006c) in Korean populations, 0.128 (Kawano et al, 2002) to 0.168 (Shimoyama et al, 2009) in Japanese populations, 0.191 in a Chinese Han population (Wang et al, 2010), and 0.227 in a Turkish population (Telci et al, 2011). Our results on the allele frequency were similar to those of studies conducted in East Asian populations, but not to that seen in the study conducted in the Turkish population.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In previous studies, the frequencies of the A allele in the G-395A SNP varied from 0.155 (Kim et al, 2008) to 0.171 (Rhee et al, 2006c) in Korean populations, 0.128 (Kawano et al, 2002) to 0.168 (Shimoyama et al, 2009) in Japanese populations, 0.191 in a Chinese Han population (Wang et al, 2010), and 0.227 in a Turkish population (Telci et al, 2011). Our results on the allele frequency were similar to those of studies conducted in East Asian populations, but not to that seen in the study conducted in the Turkish population.…”
Section: Discussionmentioning
confidence: 93%
“…The identification of SNPs in the human KLOTHO gene is currently one of the most active areas of research. So far, more than 10 SNPs have been identified in the human KLOTHO gene, and linked to fasting glucose (Rhee et al, 2006b), coronary artery disease (Imamura et al, 2006;Rhee et al, 2006a), stroke (Kim et al, 2006), bone mineral density (Kawano et al, 2002), and kidney stone (Telci et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced bone mass and high risk for osteoporotic fractures as a consequence of PTH and vitamin D abnormalities have also been documented in calcium stone formers [12,13,14,15], as well as a contributing role of FGF-23 and KLOTHO gene polymorphism in the pathogenesis of calcium nephrolithiasis [16,17]. Therefore, FGF-23 and KLOTHO are likely to influence the vitamin D status in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that antiaging gen, klotho, is important in renal aging and OS-induced renal damage. The klotho gene encodes the klotho protein, a single transmembrane protein of the beta-glycosidase family [31]. Mice overexpressing klotho exhibit an extension in lifespan and resistance to oxidative injury.…”
Section: Hypertension Hypercholesterolemia Obesity and Aging Inmentioning
confidence: 99%